Environmental pollution mitigation through planning urban strategies in Vicente Paúl, Guayaquil. - Zárate Zavala, Diana Fernanda; Almache Carranza, Katherine Yamile; Fajardo Zavala, Karla Cristina; Jiménez Alvarado, David Gabriel; Morocho Zambrano, Denisse Adriana (Artes: Architecture, Technology and Sustainability, 2024)
Environmental pollution is a phenomenon that affects the quality of life of living beings and ecosystems on planet Earth; currently, the Vicente Paul sector of the city of Guayaquil presents various problems of environmental pollution, mainly because of informal trade, lack of green areas and poor waste management; in turn, These problems are triggered by the absence of equipment necessary to meet the needs of users. The objective of this study is to design an environmental mitigation plan to improve the quality of life of the inhabitants of the sector. A quantitative methodology was used to calculate the percentage of existing green areas in the study area through the use of the ArcGIS program. In addition, a visit to the sector was made to identify the causes of pollution to develop later a comparative analysis based on the 12 Criteria that Determine a Good Public Space.